Motor skills problems in Parkinson Disease - Anna Maria Dobosiewicz; Szymon Kwiatkowski; Paulina Miętkowska; Agnieszka Marszałek; Sylwia Wendland (Kazimierz Wielki University, 2017)
Parkinson Disease is one of the most common neurodegenerative disease. The average age in which PD occur is 54-58 years but the scientists note that Parkinson Disease can also appear in age of 30 or in age of 80.  Patients which are suffering from Parkinson Disease can be described by lots of  symptoms. The most problematic in daily living are gait and balance disorders (motor skills problems). The purpose of the article is to show the possible ethiopatogenesis of gait and balance disorders and to analyse the disorders  closely/narrowly.